2021
DOI: 10.1016/j.omtm.2021.02.024
|View full text |Cite|
|
Sign up to set email alerts
|

Voluntary wheel running complements microdystrophin gene therapy to improve muscle function in mdx mice

Abstract: We tested the hypothesis that voluntary wheel running would complement microdystrophin gene therapy to improve muscle function in young mdx mice, a model of Duchenne muscular dystrophy. mdx mice injected with a single dose of AAV9-CK8-microdystrophin or vehicle at age 7 weeks were assigned to three groups: mdxRGT (run, gene therapy), mdxGT (no run, gene therapy), or mdx (no run, no gene therapy). Wild-type (WT) mice were assigned to WTR (run) and WT (no run) groups. WTR and mdxRGT performed voluntary wheel run… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 72 publications
2
26
0
Order By: Relevance
“…Further, in the diaphragm, GT2 can result in a high degree of force production when prolonged endurance exercise is applied but the addition of running to animals treated with this construct decreases mitochondrial respiration. These findings demonstrate that prolonged (52 weeks) voluntary wheel running and a microdystrophin construct structure with or without the nNOS binding site in mdx mice will sustain the functional benefits we reported for microdystrophin combined with short-term (21 weeks) voluntary wheel running in mdx mice (Hamm et al, 2021). Our findings further demonstrate that prolonged voluntary wheel running complemented the functional improvements provided by both microdystrophin constructs but also revealed the unique benefits of each to dystrophic muscle.…”
Section: Discussionsupporting
confidence: 75%
“…Further, in the diaphragm, GT2 can result in a high degree of force production when prolonged endurance exercise is applied but the addition of running to animals treated with this construct decreases mitochondrial respiration. These findings demonstrate that prolonged (52 weeks) voluntary wheel running and a microdystrophin construct structure with or without the nNOS binding site in mdx mice will sustain the functional benefits we reported for microdystrophin combined with short-term (21 weeks) voluntary wheel running in mdx mice (Hamm et al, 2021). Our findings further demonstrate that prolonged voluntary wheel running complemented the functional improvements provided by both microdystrophin constructs but also revealed the unique benefits of each to dystrophic muscle.…”
Section: Discussionsupporting
confidence: 75%
“…The procedures for in vivo muscle testing were recently published [22]. Briefly, at the end of the study, following both running wheel and metabolism measurements, body weight was determined, and mice were anesthetized with isoflurane (VetOne Fluriso, Boise, ID, USA) and placed on the temperature-controlled platform (40 • C) of the contractile apparatus (ASI), as described.…”
Section: In Vivo Muscle Function Testingmentioning
confidence: 99%
“…The mouse tail was taped (M3, St. Paul, MN, USA) loosely to the platform to keep it clear of the foot pedal. In vivo plantarflexor torque-frequency and fatigue assays were determined as described in Hamm et al [22]. Dynamic Muscle Control (DMC) software controlled the timing and frequency of the stimulations and collection of torque.…”
Section: In Vivo Muscle Function Testingmentioning
confidence: 99%
“…On the other hand, exercise can be used to build muscular strength and endurance. Hamm et al [ 37 ] proposed that a threshold could be established to guide appropriate exercise prescription for individuals with muscular atrophy. Kimura et al [ 38 ] demonstrated that immobility might minimize the muscle fiber necrosis in instances with muscular dystrophy.…”
Section: Discussionmentioning
confidence: 99%